The Influence of Binary Modulations in OTDM - Munster, Petr; Sifta, Radim; Tejkal, Vladimir; Filka, Miloslav (Communications - Scientific Letters of the University of Zilina, 2013)
In this paper we propose a simulation test using different binary modulation formats in optical network based on the Optical Time Division Multiplexing (OTDM). OTDM in optical networks is used for high speed data generation in point-to-point networks. Dispersion and nonlinearities in optical fibers can cause transmission disturbances, which can influence the throughput of the transmission system and maximal achievable distance. Basic modulation formats RZ and NRZ with new CRZ and CSRZ formats were tested in OTDM simulation model.
Keywords: OTDM; modulation; RZ; NRZ; CSRZ; CRZ; BER; Q-factor